Comic book collections for libraries - Fagan, Bryan D.; Fagan, Jody Condit 1976-. (Santa Barbara, Calif. Libraries Unlimited, 2011)
This book will help librarians extend literary graphic novel collections to attract a large, untapped group of comic book readers with a sure-to-be-popular comic book collection
Keywords: Libraries -- Special collections -- Comic books, strips, etc; Comic books, strips, etc. -- Bibliography -- Methodology; Libraries -- Special collections -- Graphic novels; Graphic novels -- Bibliography -- Methodology; Language arts -- Discipline -- Library and Information Science; Language arts -- Discipline -- Reference